La migración y su relación con el empleo informal en la Región de Loreto 2019 – 2022 - Noriega Piña, Rocio del Pilar (2024)
Migration is presented as a social-demographic phenomenon that has accompanied humanity since the beginning of its history, being key to the benefit and development of societies, frequently happening between nearby localities. Various factors cause the movement of people from one place of origin to another, without a doubt the main factor is to improve living conditions. In this sense, the objective of this research is to determine the relationship that exists between migration and informal employment in the Loreto region during the period 2019 - 2022. Since the lack of educational, employment, social opportunities, among others, in Different places, especially in rural areas, encourage residents to migrate to more developed cities. For this, a quantitative methodology of a non-experimental nature and correlational design was used, and it was found that migration has a significant relationship with informal employment in the Loreto region in the period studied and this relationship is 73%, and this has theoretical consistency according to our background and theoretical foundations.